URGENSI KOMPETENSI GURU DALAM PENGUKURAN DAN PENILAIAN - Awi' Farhun; Kurnia Rahmawati; Rahma Dyas Putri Hamidah; Retno Fatmawati; Sahidna Ahmad Rosyid (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
Teachers play an important role in creating the nation's next generation who are highly dedicated to the nation and religion, so teachers need to pay attention to mastering teacher competence. With optimal mastery of teacher competence, it can create harmony in educational institutions in the form of realizing educational goals, increasing the competence and quality of teacher human resources, as well as creating quality student human resources and being able to foster public confidence about the importance of education. With the competence possessed by the teacher, it can influence how the teacher is in the process of measuring and assessing students. This research uses library research, the method used is literature study. Literature research is research that examines different reference books, and the results of previous similar research help in obtaining a theoretical basis for the problem under study. The literature study process is carried out by reviewing the literature and analyzing related topics that are combined. Literature search can use sources in the form of journals, books, dictionaries, documents, magazines and other sources without conducting field research. The results of this study indicate that teacher competence in measurement and assessment is very important in ensuring the success of the measurement and assessment process. Teachers who have good competence in terms of pedagogic, professional, personal, and social can have a positive and significant impact on student learning outcomes. In addition, teachers who have personal competence can also assist in the moral development of students